ALTERNATIF SPESIFIKASI BINA MARGA CAMPURAN ASPAL PANAS - M Sjahdanulirwan (Direktorat Bina Teknik Jalan dan Jembatan, 1997)
Unsuitable mix design/specification can be treated as a loss because it can cause defect to pavement layer. Improvement of Bina Marga specification, especially on surface layers of AC (asphalic concrete) and Hot Rolled and binder/base course of AC is intended to avoid that unnecessary loss. This proposed alternative specification of asphalt hot mix is set up y considering the practical matters and to perform the change to the old specification as less as possible. This concept is not the one officially submitted to Bina Marga, but to represent an idea/alternative concept for furhter discussion. The change and improvement cover anticipation of plastic flow defects, accomodation of viscous elastic characateristics road existing condition factor, overlay dimension, requirement for heavy traffic, and selection of more efficient and rational parameters and values of Marshall. For AC surface layer, there is a reduction in the number of aggregate gradation, while for Hot Rolled the selection of aspalt content based on total mix is proposed.